Pengaruh Modul Literasi Membaca Berbasis Kearifan Lokal Terhadap Membaca Pemahaman Siswa Sekolah Dasar - Ramadani, Shalamat; Kurniaman, Otang; Sari, Intan Kartika (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
This research is motivated by the importance of understanding literacy as a reference in students' understanding in their combined learning activities by using modules that are referenced in the context of local wisdom to increase their knowledge horizons. This research was conducted to examine the effect of local wisdom-based modules on elementary school students. The method in this study was carried out through an experiment where the design pattern was Pre-Experimental One Group Posttest-Posttest . The sample consisted of 22 class V students from one of the elementary schools in the Tarai Bangun area, Kampar, Riau. Data was collected through experiments using pretest and posttest questions given in the form of multiple choice questions. The research results showed a significant increase in students' reading comprehension after implementing the literacy module that adopted local values, where the posttest average score (78.64 ) was significantly higher than the pretest average score (66.82). Statistical analysis also confirmed that the pretest and posttest results were significantly different (p < 0.05 ) , previously a normality test and homogeneity test had been carried out and there were normal and homogeneous value results, in the N-Gain test which showed an increase in reading comprehension in the category medium (0.3660). These findings illustrate that the implementation of local wisdom-based reading literacy modules has an impact on elementary school students' reading comprehension skills.